A PROPOSED SYLLABUS FOR ENGLISH COURSE FOR STUDENTS OF INDUSTRIAL ENGINEERING, INSTITUT SAINS & TEKNOLOGI AKPRIND, YOGYAKARTA - Ambawani, Suprih (LearnING Journal, 2014)
This study develops an English syllabus for the Industrial Engineering Department at InstitutSains&TeknologiAkprind, Yogyakarta since there is no appropriate syllabus available. The English syllabus is developed based on the educational research and development (R and D). The model used is adopted from Richards Model on Course Development (2001). The finding shows that a topic-based syllabus is appropriate for English course for students of Industrial Engineering of InstitutSains&Teknologi AKPRIND, Yogyakarta. The syllabus focuses on reading skill. The subjects being discussed are the topics related to the students field of study. The format syllabus consists of following aspects: 1) competence standard, 2) basic competence, 3) indicator, 4) materials, 5) learning activities, 6) assessments, 7) time allotment and 8) sources of the materials. In the implementation of this syllabus, it is recommended that English lecturer should collaborate with the subject specialists to get clear description of the subject being discussed; a discussion on the proposed syllabus attended by the English lecturers also needs to be done to socialize the product.